Microscopic changes in ovaries in relation to inflammation mediators of blood plasma in normal and superovulated rats - Gopalsamy, Banulata (2013)
Superovulation is an important treatment widely used in transgenic animals and in breeding industry. However, many problems on ovulation, fertilization, embryo recovery and viability rates were encountered when superovulation treatment was carried out. The study was carried out to evaluate the difference in the follicular development and inflammatory mediators of rats in the different phases of the oestrous cycle and to compare the changes that occur in superovulated rats and control rats. Six rats (n=6) from each phase of the oestrus cycle (dioestrus, proestrus, oestrus and metoestrus) were euthanised to observe the inflammatory changes that takes place throughout the cycle. In another experiment, rats were administered exogenous gonadotropin to superovulate and the rats were sacrificed 8 hour post hCG (n=6), 18 hours post hCG (n=6) and control rats (n=6) were euthanised at the oestrus phase of the cycle. Serial histological sections of ovaries were made toobserve the follicle development that occurs within the ovaries and Enzyme linked immunosorbent assay (ELISA) was carried out to analyse the inflammatory mediators in the blood plasma. Data were subjected to statistical analysis using SPSS software version 16.0. In the experiment to study the normal oestrous cycle, the ovarian weight was highest during the proestrus stage as many large follicles were present at this stage. The number of healthy and unhealthy follicles were relatively unaltered throughout the cycle but the diameters of large follicles increased significantly (P<0.05) from dioestrus to proestrus. Plasma Interleukin 8 (IL-8) and Nerve Growth Factor (NGF) was significantly (P<0.05) increase during proestrus but IL-8 level reduced in the next phases whereas NGF was maintained at a high level until the end of the cycle. Prostaglandin E2 (PGE2) concentration was however consistent throughout the cycle. In another experiment to study the inflammatory process in superovulated rats, the highest ovarian weight was recorded in 8 hours post hCG group as most of the large follicles were present in those ovaries. The number of healthy large follicles were significantly increased (P<0.05) in superovulated rats (both 8 hours post hCG and 18 hours post hCG groups) compared to control rats but the diameter of the follicles were not significantly different (P>0.05) in superovulated and control rats. The level of IL 8 was significantly increased (P<0.05) in 8 hours post hCG rats but PGE2 and NGF levels were not significantly different (P>0.05) than control rats. The outcome of this study showed that IL-8 had significantly (P<0.05) higher levels of production during proestrus and in 8 hours post hCG rats compared to control rats. The other mediator remains the same throughout the cycle and is not different in superovulated rats from control rats. Since only IL-8 was increases in superovulated rats it does not provide enough evidence to conclude if the inflammation level were increased when rats were superovulated. Therefore, further research on other inflammatory markers should be carried out to study the inflammation process that occurs as a result of the superovulatory treatment.